Flexible Budgets and its Variances under The Corona Pandemic Covid – 19 (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The research aims to explain the role of the flexible budget in assessing the feedback resulting from deviations by comparing the actual results with the planned performance in light of the economic crisis that the world witnessed during the spread of Corona disease. As most companies, including the Electronic Industries Company, face the problem of controlling production costs and are trying hard to reduce these costs to the lowest level starting from measuring these costs and allocating them and distributing them to products. This helps in controlling deviations and thus the flexible budget becomes a tool that helps in controlling elements Costs